Cost-effective scarless cholecystectomy using a modified endoscopic minimally invasive reduced appliance technique (Emirate) - Hassan, Iyad; Hassan, Lina; Alsalameh, Mohammad; Abdelkarim, Hamza; Hassan, Wiam (Frontiers in Surgery, 2023)
Abstract The current gold-standard surgical treatment for symptomatic gallstone disease is the conventional four-port laparoscopic cholecystectomy (CLC). In recent years, however, celebrities and social media have altered people's attitudes regarding surgery. Consequently, CLC has undergone several changes to reduce scarring and improve patient satisfaction. In this case-matched control study, the cost-effectiveness of a modified endoscopic minimally invasive reduced appliance technique (Emirate) that uses less equipment and three 5 mm reusable ports only at precisely specified anatomical sites was compared to CLC. Methods Single-center retrospective matched cohort analysis including 140 consecutive patients treated with Emirate laparoscopic cholecystectomy (“ELC-group”), matched 1:1 by sex, indications for surgery, surgeon expertise, and preop bile duct imaging, with 140 patients receiving CLC in the same period of time (“CLC group”). Results We performed a retrospective case-matched review of 140 patients who had Emirate laparoscopic cholecystectomy for gallstones between January 2019 and December 2022. The groups included 108 females and 32 males with an equal ratio of surgical expertise—115 procedures were performed by consultants and 25 by trainees. In each group, 18 patients had preoperative MRCP or ERCP and 20 had acute cholecystitis as indications for surgery. Preoperative characteristics such as age (39 years in the Emirates group and 38.6 years in the CLC group), BMI (29.3 years in the Emirates group and 30 years in the CLC group), stone size, or liver enzymes showed no statistical difference between the two groups. In both groups, the average hospital stay was 1.5 days, and there was no conversion to open surgery, nor was there any bleeding requiring blood transfusion, bile leakage, stone slippage, bile duct injury, or invasive intervention postoperatively. When compared to the CLC group, the ELC group had significantly faster surgery times (t-test, p = 0.001), lower levels of the bile duct enzyme ALP (p = 0.003), and much lower costs (t-test, p = 0.0001). Conclusion The Emirate laparoscopic cholecystectomy method is a safe alternative to the traditional four-port laparoscopic cholecystectomy that is also much faster and less expensive.